The Beveled Rim Technique for Labral Reconstruction - Ady H. Kahana-Rojkind, M.D.; Jessica C. Keane, B.S.; Yasemin E. Kingham, B.A.; Roger Quesada-Jimenez, M.D.; Tyler R. McCarroll, M.D.; Benjamin G. Domb, M.D. (Arthroscopy Techniques)
Arthroscopic trimming of the acetabular rim in labral reconstruction is used to create a suitable bony surface with adequate blood flow, thereby promoting the biological conditions necessary for the healing of the labrum. The aim of this Technical Note is to present an improvement to the current arthroscopic rim preparation technique. The technique involves creating an inward beveled acetabular rim to increase the contact area of the graft on the femoral head, in order to create a greater suction seal and strategically distribute the forces generated during femoral head distraction onto both the labral graft and the acetabular rim.